2018
DOI: 10.31021/acs.20181107
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Study on Impact of Temperature in Malaria Disease Transmission Dynamics

Abstract: Malaria is one of the most common mosquito borne diseases. Temperature is an important factor which affects the life cycle of the mosquitoes and transmission dynamics of the malaria disease. In the present work, we use SEIR compartmental model for the human population and LSEI compartmental model for mosquito population taking temperature dependent parameters. Basic reproduction number, R 0 of the model is computed using Next Generation Matrix Method. Stability of the disease free equilibrium and the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Likewise, as temperatures increased from 15 to 35 °C, the longevity of Anopheles mosquitoes decreased. This is similar to other studies [54][55][56] that reported that mosquito longevity and mortality are negatively affected at higher temperatures.…”
Section: Effects Of Temperature On Adult Mosquitoes 421 Life-history Traitssupporting
confidence: 92%
“…Likewise, as temperatures increased from 15 to 35 °C, the longevity of Anopheles mosquitoes decreased. This is similar to other studies [54][55][56] that reported that mosquito longevity and mortality are negatively affected at higher temperatures.…”
Section: Effects Of Temperature On Adult Mosquitoes 421 Life-history Traitssupporting
confidence: 92%
“…In this paper, a malaria transmission model with temperature-and rainfall-dependent parameters is studied. The present model differs from the models proposed by Mukhtar et al [30] and Bhuju et al [33] in that it assumes that interaction coefficients between humans and mosquitoes are constants and also ignores the exposed class in the mosquito population. In addition, the stability analysis of the steady states is also carried out.…”
Section: Introductionmentioning
confidence: 81%
“…It is assumed that mosquitoes do not die from malaria due to their short lifespan. Adult female Anopheles mosquitoes lay eggs at a temperature-dependent rate LðTÞ, and the aquatic mosquito population increase is constrained by the carrying capacity of the environment K [33]. Aquatic mosquitoes mature and develop into adult mosquitoes at a temperature-and rainfall-dependent rate λ ðT, RÞ.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models are useful to study the transmission dynamics of infectious disease and to conduct control strategies against the disease [3,4,8,9,12,13,14]. J. Singh et al used the successive approximation method for short term forecast of infected population in India [18].…”
Section: Introductionmentioning
confidence: 99%